Nuclear Imaging in Dentistry -A novel modality to explore - Dathar, Sahithi; Reddy, Sudhakara; Koneru, Jyothirmai; Preethi, M; Guvvala, Satheesh (International Journal of Health, 2015)
Nuclear imaging is an exceptional branch of medical science that has been evolved in the latest decades in early diagnosis of a disease. The main underlying principle is that radioisotopes are injected in the body and emits gamma rays which are detected by special image receptors. Various nuclear imaging modalities include Scintigraphy, SPECT (Single photon emission computed tomography) and PET (Positron emission tomography) which can assess any functional changes that occur within a diseased cell. This article has essentially dealt with the fundamental principles of various nuclear imaging modalities and their applications in oral and maxillofacial region.